Anode and secondary battery

By adopting a negative electrode active material layer with a double-layer structure in the secondary battery, using the combination of silicon active material and natural graphite, and adjusting the orientation index through magnetic alignment, the problem of insufficient fast charging performance is solved, faster lithium ion penetration and diffusion are achieved, and the charging speed and life of the battery is improved.

JP2025503068AActive Publication Date: 2025-01-30LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024543246
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2023-09-27
Publication Date
2025-01-30
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The prior art is difficult to improve the fast charging performance of secondary batteries without affecting battery performance.

Method used

A negative electrode active material layer is adopted with a bilayer structure, wherein the first and second layers contain silicon active material and natural graphite, respectively, with an average particle size of less than 10 μm, and the orientation index (OI) of each layer is less than 8 by magnetic alignment, so as to optimize the orientation and particle size of graphite and improve the permeation and diffusion speed of lithium ions.

Benefits of technology

By optimizing the structure and composition of the negative electrode active material layer, the fast charging performance and durability of the battery are significantly improved, the moving resistance of lithium ions is reduced, the diffusion distance of lithium ions in particles is shortened, and the rapid charging and service life of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503068000001
    Figure 2025503068000001
  • Figure 2025503068000002
    Figure 2025503068000002
  • Figure 2025503068000003
    Figure 2025503068000003
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a secondary battery, comprising: a current collector; a first negative electrode active material layer provided on the current collector; and a second negative electrode active material layer provided on the first negative electrode active material layer, the first and second negative electrode active material layers containing a silicon-based active material and natural graphite, the natural graphite having an average particle size (D50) of 10 μm or less, and the first and second negative electrode active material layers having an OI(004 / 110) of 8 or less, and a secondary battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a secondary battery and a secondary battery including the same.

[0002] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0125438, filed with the Korean Intellectual Property Office on September 30, 2022, the entire contents of which are incorporated herein by reference. [Background technology]

[0003] Secondary batteries are widely used not only in portable devices but also in electric vehicles (EVs, Electric Vehicles) and hybrid electric vehicles (HEVs, Hybrid Electric Vehicles) that are powered by electrical sources.

[0004] Such secondary batteries have the primary advantage of dramatically reducing the use of fossil fuels, as well as the advantage of not producing any by-products from the use of energy, and are therefore attracting attention as a new energy source that is environmentally friendly and can improve energy efficiency.

[0005] In general, a secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, etc. In addition, the electrodes such as the positive electrode and the negative electrode may have an electrode active material layer provided on a current collector.

[0006] As the use of secondary batteries increases, various battery performances are required. Attempts have been made to introduce additives into the active material layer to improve battery performance, but while some battery performances may be improved depending on the type of additive, other performances may be deteriorated. Therefore, there is a need for research into the selection or combination of materials to be included in the electrode that can improve the required performance of secondary batteries. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a negative electrode for a secondary battery having improved rapid charging performance, and a secondary battery including the same. [Means for solving the problem]

[0008] One embodiment of the present invention comprises: Current collector; a first negative electrode active material layer provided on the current collector; and a second negative electrode active material layer provided on the first negative electrode active material layer; Including, The first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is 10 μm or less; The first negative electrode active material layer and the second negative electrode active material layer have an OI(004 / 110) of 8 or less.

[0009] Another embodiment of the present invention provides a secondary battery comprising the above-mentioned negative electrode for secondary batteries, a positive electrode, and a separator.

[0010] Another embodiment of the present invention comprises: forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer; Including, The first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is 10 μm or less; The method for manufacturing a negative electrode for a secondary battery according to the above embodiment further includes the step of magnetically aligning the first negative electrode active material layer and the second negative electrode active material layer to adjust OI(004 / 110) to 8 or less. Effect of the Invention

[0011] According to the embodiment described herein, in a two-layered negative electrode active material layer including a silicon-based active material and graphite, the graphite orientation degree of the negative electrode active material layer is controlled and the particle size of the natural graphite is optimized, thereby maximizing the rapid charging performance. Specifically, compared to forming a single layer of the negative electrode active material layer, when the layer is formed in a two-layered structure, the thickness of each layer is formed thinner than that of a single layer, thereby improving the penetration and diffusion speed of lithium ions. In addition, the two-layered structure can be configured so that the materials of each layer are different as necessary, thereby improving the battery characteristics. Furthermore, the tortuosity and orientation degree of the negative electrode are reduced through the graphite magnetic alignment in the negative electrode, so that lithium migration in the negative electrode proceeds more smoothly. The durability, i.e., the lifespan, of the battery after magnetic alignment can be improved in the two-layered structure compared to the single-layer structure. At the same time, by using natural graphite with a small particle size in combination, the lithium diffusion distance in the particles is shortened and the charging can be accelerated. In addition, the rapid charging performance of the negative electrode can be improved by using natural graphite with a small particle size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in more detail below to help the understanding of the present invention. The present invention can be embodied in various different forms and is not limited to the embodiments described herein. In this regard, the terms or words used in the present specification and claims are not to be construed as being limited to their ordinary or dictionary meanings, but are to be construed as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor can appropriately define the concepts of terms in order to best describe his / her invention.

[0013] As used herein, terms such as "comprise", "comprise", or "have" are intended to specify the presence of stated features, numbers, steps, components, or combinations thereof, and are understood as not precluding the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0014] Furthermore, when a part such as a layer is said to be "above" another part, this does not only mean that it is "directly above" the other part, but also includes cases where there is another part between them. Conversely, when a part is said to be "directly above" another part, it means that there is no other part between them. Note that being "above" a reference part refers to being located above or below the reference part, and does not necessarily mean being located "above" in the opposite direction of gravity.

[0015] As used herein, the "weight loading ratio" of a particular layer refers to the weight percent of that layer based on the total weight of all active material layers in the electrode.

[0016] As used herein, "SOC" means state of charge.

[0017] In this specification, particle size means the average particle size represented by D50. D50 can be defined as the particle size based on 50% of the particle size distribution, and can be measured using a laser diffraction method. For example, the average particle size (D50) can be measured by dispersing particles in a dispersion medium, introducing the particles into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating the particles with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle size (D50) corresponding to 50% of the cumulative volume in the measuring device.

[0018] In this specification, a description referring only to an "active material layer" without the terms "first" and "second" can apply to both the first and second active material layers.

[0019] According to one embodiment of the present specification, a negative electrode for a secondary battery includes a current collector; a first negative electrode active material layer provided on the current collector; and a second negative electrode active material layer provided on the first negative electrode active material layer, the first and second negative electrode active material layers include a silicon-based active material and natural graphite, the natural graphite has an average particle size (D50) of 10 μm or less, and the first and second negative electrode active material layers have an OI (004 / 110) of 8 or less. In other words, the negative electrode for a secondary battery uses small-particle-size natural graphite and adjusts the graphite orientation degree of the negative electrode active material to the above range, thereby allowing lithium to move more actively within the negative electrode, thereby improving the rapid charging performance of the negative electrode. When the OI (004 / 110) of the first and second negative electrode active material layers is 8 or less, the internal structure of the negative electrode active material layer is randomized and the degree of disorder increases, which makes the movement and diffusion of lithium ions faster and easier, which is advantageous for rapid charging performance. The first and second negative electrode active material layers may have an OI(004 / 110) of 8 or less, 7 or less, or 6 or less.

[0020] The OI(004 / 110) of the first and second negative electrode active material layers is a value obtained through X-ray diffraction analysis, and can be obtained using a common method of X-ray diffraction analysis, for example, JISK 0131-1996, and can be obtained using an X-ray diffraction analyzer Bruker D4 Endeavor. In this case, the OI(004 / 110) is measured in a state where the first and second negative electrode active material layers are provided on a current collector. The OI is a value measured for the entire first and second negative electrode active material layers. The OI measured in this manner includes the properties of the negative electrode active material layers imparted by the manufacturing process, including coating and rolling, as well as the materials constituting the negative electrode active material layers, and is therefore distinguished from an OI value measured when the electrode material is in a powder state.

[0021] The OI value of the negative electrode is I 004 / I 110 It can be expressed as I 004 represents the characteristic diffraction peak area of ​​the (004) crystal plane, and I 110represents a characteristic diffraction peak area of ​​the (110) crystal plane. The (004) crystal plane has a parallel crystal structure, and the (110) crystal plane has a perpendicular crystal structure. Such characteristics indicate the degree of orientation of the graphite crystals in the negative electrode active material layer. The larger the OI value, the higher the graphite orientation, meaning that the graphite is more parallel to the measurement surface. In the embodiment, by adjusting the OI value to 8 or less, the tortuosity and orientation of the negative electrode can be reduced, and lithium ions can be easily inserted into or removed from the graphite crystal structure. The OI value may be, for example, 1 to 8, for example, 3 to 8. The OI value may be measured on an electrode after the negative electrode is prepared (a fresh negative electrode or an electrode after charge and discharge including an activation process).

[0022] In the case where the weight loading ratio of the upper layer, i.e., the second negative electrode active material layer, in forming the two-layered negative electrode active material layer is controlled to 20% to 35% relative to the total weight loading ratio of the entire negative electrode active material layer (including the first negative electrode active material layer and the second negative electrode active material layer), the thickness of the upper layer (second negative electrode active material layer) is set to 20% to 35% relative to the total thickness of the upper layer (second negative electrode active material layer) and the lower layer (first negative electrode active material layer), thereby reducing the movement distance of lithium inserted from the upper layer surface and allowing lithium to move more smoothly inside the lower layer negative electrode through the above-mentioned orientation. The weight loading ratio of the second negative electrode active material layer, which is the upper layer of the negative electrode active material layers, may be 20% to 35%, for example, 25% to 35%, or 28% to 32%, based on the total of the upper and lower layers. Since the weight loading ratio of each layer is proportional to the thickness of each layer, the weight loading ratio can be confirmed from the thickness of each layer.

[0023] According to one embodiment, the thickness of the second negative electrode active material layer may be 40% to 60%, for example 45% to 55%, specifically 50%, of the thickness of the first negative electrode active material layer.

[0024] In this specification, the boundary between the first and second negative electrode active material layers can be confirmed by measuring the cross section of the electrode. For example, the electrode cross section is cut by ion milling, and the cross sectioned electrode is measured by a scanning electron microscope, whereby the boundary between the two layers can be confirmed.

[0025] According to one embodiment, the first negative electrode active material layer and the second negative electrode active material layer may have different silicon-based active material contents. According to one example, the second negative electrode active material layer may have a higher silicon-based active material content than the first negative electrode active material layer. In this way, even if the second negative electrode active material layer contains a large amount of silicon-based active material, the thickness or weight loading ratio of the second negative electrode active material layer may be set to 20% or more to prevent the energy density from becoming too low. According to another embodiment, the first negative electrode active material layer and the second negative electrode active material layer may have the same silicon-based active material content.

[0026] According to one embodiment, the average particle size (D50) of the natural graphite may be 10 μm or less, 9 μm or less, or 6 μm to 9 μm. Although the average particle size (D50) of general natural graphite is more than 10 μm, in the above embodiment, the smaller the average particle size (D50) is, 10 μm or less, the shorter the diffusion distance of lithium ions is, so that it is advantageous to improve the fast charging characteristics by accelerating the penetration and diffusion of lithium ions. Specifically, the larger the particle size of the natural graphite, the longer the conversion distance of lithium inside the particle, so that the fast charging is deteriorated, and conversely, the smaller the particle size, the shorter the lithium diffusion distance, so that it is more advantageous to improve the fast charging. As an exemplary method for adjusting the particle size of the natural graphite, a method can be used in which flake natural graphite is spheroidized and the surface of the spheroidized natural graphite is carbon-coated to reduce the large specific surface area. The flake natural graphite can be spheroidized by air flow classification. The surface carbon coating treatment may be performed by disposing a precursor on the modified spheroidized natural graphite and then performing a heat treatment. The precursor is a precursor for carbon coating the surface of natural graphite, and a material such as pitch may be used as a non-limiting example.

[0027] According to one embodiment, the first and second negative electrode active material layers may further include artificial graphite. The artificial graphite may have an average particle size (D50) of 15 μm to 50 μm. When the average particle size (D50) of the artificial graphite is 15 μm or more, the binder is uniformly applied to the active material surface, thereby improving the negative electrode adhesion to the current collector, and when it is 50 μm or less, lithium ions are easily diffused, thereby improving the negative electrode rapid charging performance.

[0028] Since artificial graphite is an assembled secondary particle, it is difficult to adjust the particle size to 10 μm or less. In addition, even if the size of assembled (primary particles assembled into secondary particles) artificial graphite is 10 μm, it does not have a good effect on the adhesion to the current collector. The reason is that the particles are small, so there is a large amount of dead binder (a binder that is sandwiched between particles and cannot act as an adhesive), which adversely affects the adhesion. In addition, the smaller the particle size of artificial graphite, the more densely the particles are located in the electrode, and the more densely packed the electrode is after rolling, which is not advantageous for fast charging performance. A dense structure increases the tortuosity in the electrode, i.e., the distance that lithium ions can travel, and is disadvantageous for fast charging performance.

[0029] According to one embodiment, the first and second negative electrode active material layers may each contain 10 parts by weight to 50 parts by weight, for example 15 parts by weight to 45 parts by weight, or 20 parts by weight to 45 parts by weight, of natural graphite based on 100 parts by weight of the negative electrode active material.

[0030] According to an embodiment, the first and second negative electrode active material layers may each contain 50 to 89 parts by weight, for example, 52 to 85 parts by weight, 55 to 80 parts by weight, or 58 to 72 parts by weight of artificial graphite based on 100 parts by weight of the negative electrode active material. If the content of artificial graphite is higher than the content of natural graphite, it may be advantageous for improving fast charging performance.

[0031] According to one embodiment, the content of natural graphite in the second negative electrode active material layer is less than the content of natural graphite in the first negative electrode active material layer. For example, the content of natural graphite in the second negative electrode active material layer may be 25 parts by weight to 35 parts by weight with respect to 100 parts by weight of graphite in the second negative electrode active material layer, and the content of natural graphite in the first negative electrode active material layer may be 35 parts by weight to 45 parts by weight with respect to 100 parts by weight of graphite in the first negative electrode active material layer. Artificial graphite is advantageous in improving rapid charging performance compared to natural graphite. Meanwhile, natural graphite has a larger capacity than artificial graphite, and can increase energy density and increase adhesion to a negative electrode current collector. Therefore, while it is difficult to simultaneously secure the fast charging performance of artificial graphite and the high energy density and adhesive strength to the electrode of natural graphite with a single layer structure, the two-layer structure of the present invention relatively increases the natural graphite content of the first negative electrode active material layer disposed closer to the negative electrode current collector, and relatively increases the artificial graphite content of the second negative electrode active material layer, thereby improving the fast charging performance, energy density, and adhesive strength to the current collector.

[0032] In one embodiment of the present specification, the silicon-based active material is SiO x (0≦x<2), SiM y (M is a metal, 1≦y≦4) and Si / C. The silicon-based active material may be one type only, or two or more types may be included together. When both of the two negative electrode active material layers contain a silicon-based active material, the two active material layers may use the same type of silicon-based active material, or different types or different combinations of silicon-based active materials.

[0033] In one embodiment of the present specification, the silicon-based active material may be contained in an amount of 1 part by weight to 40 parts by weight, for example, 1 part by weight to 20 parts by weight, based on 100 parts by weight of the total active material contained in the negative electrode active material layer including the silicon-based active material. The silicon-based active materials in the first and second negative electrode active material layers may be contained in the same amount or in different amounts.

[0034] As the silicon-based active material, SiO xThe active material containing (0 ≦ x < 2) is SiO x It may be silicon-based composite particles containing (0 < x < 2) and pores.

[0035] In this specification, the composite particle or composite means that two or more materials or substances are physically aggregated without chemical bonding.

[0036] The above SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particles. The above SiO x (0 < x < 2) may be in a form containing Si and SiO2, and the Si may form a phase. That is, the above x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based composite particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0037] The silicon-based composite particles may further contain at least one of a magnesium (Mg) compound and a lithium (Li) compound. The magnesium (Mg) compound and the lithium (Li) compound can correspond to the matrix in the silicon-based composite particles.

[0038] The magnesium (Mg) compound and / or lithium (Li) compound may be present inside and / or on the surface of the SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the magnesium (Mg) compound and / or lithium (Li) compound.

[0039] The Mg compound may include at least one selected from the group consisting of magnesium (Mg) silicate, magnesium (Mg) silicide, and magnesium (Mg) oxide. The magnesium (Mg) silicate may include at least one of Mg2SiO4 and MgSiO3. The magnesium (Mg) silicide may include Mg2Si. The Mg oxide may include MgO.

[0040] In one embodiment of the present specification, the magnesium (Mg) element may be included in an amount of 0.1 wt% to 20 wt%, or 0.1 wt% to 10 wt%, based on a total of 100 wt% of the silicon-based active material. Specifically, the magnesium (Mg) element may be included in an amount of 0.5 wt% to 8 wt% or 0.8 wt% to 4 wt%. If the above range is satisfied, the magnesium (Mg) compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during charging and discharging of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0041] The lithium (Li) compound may include at least one selected from the group consisting of lithium (Li) silicate, lithium (Li) silicide, and lithium (Li) oxide. The lithium (Li) silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The lithium (Li) silicide may include Li7Si2. The lithium (Li) oxide may include Li2O.

[0042] In one embodiment of the present invention, the lithium (Li) compound may include a form of lithium silicate. The lithium silicate is Li a S b O c(2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate can exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-based composite particles, and the amorphous lithium silicate is Li a Si b O c It may be in the form of (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.

[0043] In one embodiment of the present specification, the Li element may be contained in an amount of 0.1% by weight to 20% by weight, or may be contained in an amount of 0.1% by weight to 10% by weight based on 100% by weight of the silicon-based active material. Specifically, the Li element may be contained in an amount of 0.5% by weight to 8% by weight, and more specifically, may be contained in an amount of 0.5% by weight to 4% by weight. When the above range is satisfied, the Li compound can be contained in an appropriate content within the silicon-based active material, so that the change in the volume of the negative electrode active material can be easily suppressed during charging and discharging of the battery, and the discharge capacity and initial efficiency of the battery can be improved.

[0044] The content of the Mg element or Li element can be confirmed by ICP (inductively coupled plasma) analysis. After accurately sampling a certain amount (about 0.01 g) of the negative electrode active material for the ICP analysis, it is transferred to a platinum crucible, nitric acid, hydrofluoric acid, and sulfuric acid are added, and it is completely decomposed on a hot plate. Then, using an inductively coupled plasma optical emission spectrometry (ICPAES, Perkin-Elmer 7300), the intensity of a standard solution (5 mg / kg) prepared using a standard solution at the characteristic wavelength of the Mg element or Li element is measured to create a calibration curve. Then, the pretreated sample solution and the matrix sample are introduced into the instrument, the intensities of each are measured to calculate the actual intensity, and after calculating the concentration of each component by comparing with the created calibration curve, the Mg element or Li element content of the manufactured silicon-based active material is analyzed by converting so that the total sum becomes the theoretical value.

[0045] In one embodiment of the present specification, a carbon layer may be provided on the surface and / or inside the pores of the silicon-based composite particles. The carbon layer imparts electrical conductivity to the silicon-based composite particles, and the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material including the silicon-based composite particles may be improved. The total weight of the carbon layer may be 5% by weight to 40% by weight based on a total of 100% by weight of the silicon-based composite particles.

[0046] In one embodiment of the present specification, the carbon layer may include at least one of amorphous carbon and crystalline carbon.

[0047] The average particle size (D50) of the silicon-based active material may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the average particle size (D50) of the silicon-based active material is within this range, the side reaction between the silicon-based composite particles and the electrolyte is controlled, and the discharge capacity and initial efficiency of the battery can be effectively realized.

[0048] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by the laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.

[0049] The silicon-based active material containing Si / C is a composite of Si and C, and is distinguished from silicon carbide, which is abbreviated as SiC. The silicon carbon composite may be a composite of silicon and graphite, or may have a structure in which a core of a composite of silicon and graphite is surrounded by graphene or amorphous carbon. The silicon dispersed in the silicon carbon composite may be nanosilicon.

[0050] In one embodiment of the present specification, the negative electrode active material in 100 parts by weight of each negative electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and still more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0051] According to a further embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon-based active material and the carbon-based active material.

[0052] The negative electrode binder may play a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material particles and the negative electrode current collector. The negative electrode binder may be any one known in the art, and non-limiting examples thereof include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or various copolymers thereof.

[0053] The negative electrode binder may be included in an amount of 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 20 parts by weight, and more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0054] The negative electrode active material layer may not include a conductive material, but may further include a conductive material if necessary. The conductive material included in the negative electrode active material layer is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples thereof include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. The content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0055] For the purposes of the present invention, when the carbon-based active material is graphite, such as natural graphite or artificial graphite, the weight parts of graphite used as the carbon-based active material are not taken into account when defining the total weight parts of the conductive material. Similarly, when the conductive material selected according to the negative electrode is graphite, the weight parts of the conductive material described when defining the total weight parts of the carbon-based negative electrode active material are not included. Thus, when graphite is selected as both the carbon-based negative electrode active material and the negative electrode conductive material, the total weight parts of graphite correspond to the sum of the weight parts of graphite used as the carbon-based negative electrode active material and the weight parts of graphite used as the negative electrode conductive material.

[0056] According to an example, the conductive material contained in the negative electrode active material layer may be carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fiber such as carbon fiber or metal fiber; or conductive tube such as carbon nanotube.

[0057] In one embodiment of the present specification, the thickness of the first negative electrode active material layer may be 1 μm or more and 50 μm or less, for example, 2 μm or more and 40 μm or less, 5 μm or more and 30 μm or less, or 10 μm or more and 25 μm or less; the thickness of the second negative electrode active material layer may be 5 μm or more and 100 μm or less, for example, 10 μm or more and 80 μm or less, 20 μm or more and 60 μm or less, or 25 μm or more and 50 μm or less. The sum of the thicknesses of the first negative electrode active material layer and the second negative electrode active material layer may be 6 μm or more and 150 μm or less, 50 μm or more and 140 μm or less, or 80 μm or more and 120 μm or less.

[0058] In one embodiment of the present specification, the negative electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the current collector can be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. Specifically, transition metals that adsorb carbon well, such as copper and nickel, can be used as the current collector. The thickness of the current collector can be 1 μm to 500 μm, but the thickness of the current collector is not limited thereto.

[0059] A further embodiment herein provides a secondary battery comprising an anode, a cathode and a separator according to the previous embodiment.

[0060] In one embodiment of the present specification, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material. The positive electrode active material layer may have a thickness of 20 μm or more and 500 μm or less.

[0061] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. The positive electrode current collector may usually have a thickness of 1 to 500 μm, and fine irregularities can be formed on the collector surface to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0062] In one embodiment of the present specification, the positive electrode may include a lithium composite transition metal compound including nickel (Ni) and cobalt (Co) as an active material. The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include nickel in an amount of 80 mol % or more, for example, 80 mol % or more and less than 100 mol %, of metals other than lithium.

[0063] In one embodiment, the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0064] According to a further embodiment of the present specification, the positive electrode active material layer according to the above embodiment may further include a positive electrode binder and a conductive material.

[0065] The positive electrode binder may play a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material particles and the positive electrode current collector. As the positive electrode binder, those known in the art may be used, and non-limiting examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0066] The positive electrode binder may be included in an amount of 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, and more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.

[0067] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not undergo chemical changes in the battery and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0068] Specifically, in one embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). The conductive material may be included in an amount of 0.1 to 2 parts by weight based on 100 parts by weight of the composition for positive electrode active material layer, for example, preferably 0.3 to 1.5 parts by weight, more preferably 0.5 to 1.2 parts by weight.

[0069] The positive and negative electrodes may be manufactured according to a typical method for manufacturing positive and negative electrodes, except for using the positive and negative active materials. Specifically, the active material layer forming composition containing the active material and, optionally, a binder and a conductive material may be applied to a current collector, followed by drying and rolling. In this case, the types and contents of the positive and negative active materials, binder, and conductive material are as described above. The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the active material, conductive material, and binder in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can provide excellent thickness uniformity when applied to manufacture the positive and negative electrodes. As another method, the positive electrode and the negative electrode may be produced by casting the active material layer forming composition on a separate support, peeling the composition off from the support, and laminating the resulting film on a current collector.

[0070] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to the ion movement of the electrolyte and excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0071] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0072] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0073] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0074] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.

[0075] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:

[0076] In addition to the electrolyte components, the electrolyte may further include one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0077] A further embodiment of the present specification provides a method for manufacturing a negative electrode for a secondary battery according to the above embodiment, which includes forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer, the first and second negative electrode active material layers including a silicon-based active material and natural graphite, the natural graphite having an average particle size (D50) of 10 μm or less, and further including magnetically aligning the first and second negative electrode active material layers to adjust the OI (004 / 110) to 8 or less. The magnetic alignment may be performed by coating the first negative electrode active material layer on the current collector; and coating the second negative electrode active material layer on the first negative electrode active material layer in a magnetic state. If necessary, each of the steps of coating the first and second negative electrode active material layers may further include a drying step. That is, the first negative electrode active material layer may be coated and dried in a magnetic state, and the second negative electrode active material layer may be coated and dried.

[0078] According to one embodiment, the weight loading ratio of the second negative electrode active material layer may be 20% to 35% of the weight loading ratios of the first and second negative electrode active material layers. When the weight loading ratio of the second negative electrode active material layer is 20% or more, it is advantageous for meeting the pseudo-grade cell specifications because of its high energy density.

[0079] The embodiment further includes a step of magnetically aligning the first and second negative electrode active material layers to adjust the OI to 8 or less. The degree of alignment can be controlled by magnetic alignment intensity or time, and the stronger the intensity or the longer the exposure time, the better the magnetic alignment and the lower the OI value. Thus, magnetism can be strategically applied during the above-described method to adjust the OI value of the first and second negative electrode active material layers to 8 or less.

[0080] A secondary battery according to an embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, which may be a lithium secondary battery. The lithium secondary battery has excellent fast charging performance, and may have a 3C Li plating SOC of 27% or more, preferably 28% or more or 29% or more, when a lithium coin half cell is fabricated using the negative electrode included in the secondary battery, as measured by an experimental method in the examples described below.

[0081] A further embodiment of the present invention provides a battery module including the above-mentioned secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0082] The secondary battery according to the embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics, and cycle performance, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, as well as portable devices such as mobile phones, notebook computers, and digital cameras. For example, the battery module or battery pack can be used as a power source for one or more medium- to large-sized devices including power tools, electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs), or power storage systems.

[0083] In the following, preferred embodiments are presented to aid in understanding the present invention, but the embodiments are merely illustrative of the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Such changes and modifications are naturally within the scope of the accompanying claims.

[0084] Example 1 A first negative electrode active material layer forming composition containing artificial graphite with a D50 of 21 μm, SiO and natural graphite with a D50 of 9 μm as negative electrode active materials was coated on a copper foil with a thickness of 15 μm, and then dried to form a first negative electrode active material layer. A second negative electrode active material layer forming composition containing artificial graphite with a D50 of 21 μm, SiO and natural graphite with a D50 of 9 μm as negative electrode active materials was coated on the first negative electrode active material layer, and then dried to form a second negative electrode active material layer to prepare a negative electrode. The first and second negative electrode active material layer forming compositions were coated through a magnet facility, and magnetic orientation was performed by controlling the magnet strength and total exposure time.

[0085] The compositions for forming the first and second negative electrode active material layers were prepared by mixing the above-mentioned negative electrode active material, Super C65 as a conductive material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in a weight ratio of 96 (artificial graphite / natural graphite / SiO 60 / 39 / 1):1:2:1 (first negative electrode active material layer) and 96 (artificial graphite / natural graphite / SiO 70 / 29 / 1):1:2:1 (second negative electrode active material layer), respectively, and adding water.

[0086] The loading amount of the composition for forming the second negative electrode active material layer was 30 wt % based on the total amount of the compositions for forming the first and second negative electrode active material layers, and the OI of the produced first and second negative electrode active material layers was 6.

[0087] A lithium coin half cell was manufactured by dissolving 0.5% by weight of vinylene carbonate in a mixed solution of methyl ethyl carbonate (EMC) and ethylene carbonate (EC) with a volume ratio of 7:3, and injecting an electrolyte solution in which LiPF6 was dissolved at a concentration of 1M.

[0088] OI was measured in the following manner.

[0089] The orientation index I(004) / I(110) indicates the degree to which the crystal structure in the negative active material layer is arranged in a certain direction, and can be measured by X-ray diffraction (XRD) to evaluate the direction in which the crystals are oriented in the negative active material layer. More specifically, the orientation index is an area ratio ((004) / (110)) obtained by integrating the peak intensities of the (110) and (004) planes after measuring the (110) and (004) planes of the negative active material included in the negative active material layer by XRD, and more specifically, the XRD measurement conditions are as follows:

[0090] - Target: Cu (Kα line) graphite monochromator - Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree - Measurement area and step angle / measurement time: (110) plane: 76.5 degrees < 2θ < 78.5 degrees, 0.01 degrees / 3 seconds (004) plane: 53.5 degrees < 2θ < 56.0 degrees, 0.01 degrees / 3 seconds, In the above, 2θ represents the diffraction angle.

[0091] Example 2 The same procedure as in Example 1 was carried out, except that the D50 of the natural graphite contained in the first and second negative electrode active materials was 7 μm. The loading amount of the composition for forming the second negative electrode active material was 30 wt % based on the total amount of the compositions for forming the first and second negative electrode active materials, and the OI of the prepared first and second negative electrode active material layers was 3. Compared to Example 1, the tortuosity and orientation of the negative electrode were reduced due to the magnetic alignment of the graphite in the negative electrode by increasing the exposure time to the magnet equipment.

[0092] Example 3 The same procedure as in Example 1 was repeated, except that the first and second negative electrode active material layers were prepared by using natural graphite having a D50 of 10 μm instead of natural graphite having a D50 of 9 μm, and the OI of the first and second negative electrode active material layers was adjusted to 8.

[0093] Comparative Example 1 Except that the first and second negative electrode active material layer forming compositions were not coated using a magnet device, the same procedure as in Example 1 was carried out. The loading amount of the second negative electrode active material forming composition was 30 wt % based on the total amount of the first and second negative electrode active material forming compositions, and the OI of the prepared first and second negative electrode active material layers was 14.

[0094] Comparative Example 2 The same procedure as in Example 1 was repeated, except that the natural graphite contained in the first and second negative electrode active materials had a D50 of 18 μm. The loading amount of the composition for forming the second negative electrode active material was 30 wt % based on the total amount of the compositions for forming the first and second negative electrode active material, and the OI of the first and second negative electrode active material layers was 10, as compared to Example 1, by reducing the exposure time to the magnet equipment.

[0095] Comparative Example 3 The same procedure as in Example 1 was repeated, except that the loading amount of the second negative electrode active material composition was 70 wt % based on the total amount of the first and second negative electrode active material compositions. The OI of the first and second negative electrode active material layers was 10, which was achieved by reducing the exposure time to the magnet equipment compared to Example 1.

[0096] Comparative Example 4 The same procedure as in Example 1 was carried out, except that the natural graphite contained in the first and second negative electrode active materials had a D50 of 20 μm. The loading amount of the composition for forming the second negative electrode active material was 30 wt % based on the total amount of the compositions for forming the first and second negative electrode active material, and the OI of the first and second negative electrode active material layers prepared without exposure to a magnet equipment was 22.

[0097] Comparative Example 5 The same procedure as in Example 1 was carried out, except that the first negative electrode active material layer was produced using natural graphite with a D50 of 20 μm, the degree of negative electrode orientation was adjusted to 24, and the second negative electrode active material layer was not formed. When there was a large amount of fine powder with small particle size distribution due to the material characteristics, the electrode orientation after electrode rolling increased, and the OI value increased.

[0098] The manufactured half cell was charged and discharged three times at 0.1C, and the discharge capacity of the third cycle was set as the standard at 1C. The fast charging performance was evaluated by finding the gradient change point by differentiating the output voltage due to the SOC (state of charge) change against the capacity while charging in CC mode (3C) for 15 minutes. The Li plating SOC is the SOC point at which lithium is deposited.

[0099] [Table 1]

[0100] As shown in Table 1, it was confirmed that the half cells prepared in the examples had superior fast charging performance compared to Comparative Examples 1 to 5.

Claims

1. Current collector, a first negative electrode active material layer provided on the current collector; and a second negative electrode active material layer provided on the first negative electrode active material layer; Including, the first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is 10 μm or less; the first and second negative electrode active material layers each have an OI(004 / 110) of 8 or less.

2. 2. The negative electrode for a secondary battery according to claim 1, wherein a thickness of the second negative electrode active material layer is 20% to 35% of a total thickness of the first negative electrode active material layer and the second negative electrode active material layer.

3. 2. The negative electrode for a secondary battery according to claim 1, wherein a thickness of the second negative electrode active material layer is 40% to 60% of a thickness of the first negative electrode active material layer.

4. 2. The negative electrode for a secondary battery according to claim 1, wherein the natural graphite has an average particle size (D50) of 6 μm to 9 μm.

5. The negative electrode of claim 1 , wherein the first negative electrode active material layer and the second negative electrode active material layer further contain artificial graphite.

6. 6. The negative electrode for a secondary battery according to claim 5, wherein the average particle size (D50) of the artificial graphite is 15 μm to 50 μm.

7. 2. The negative electrode for secondary batteries according to claim 1, wherein the first negative electrode active material layer and the second negative electrode active material layer each contain 1 part by weight to 40 parts by weight of a silicon-based active material based on 100 parts by weight of the negative electrode active material.

8. The silicon-based active material is SiO x (0≦x<2), SiM y 2. The negative electrode for secondary batteries according to claim 1, comprising at least one of: (M is a metal; 1≦y≦4); and Si / C.

9. 2. The negative electrode for a secondary battery according to claim 1, wherein each of the first negative electrode active material layer and the second negative electrode active material layer contains 10 parts by weight to 50 parts by weight of natural graphite based on 100 parts by weight of the negative electrode active material.

10. 2. The negative electrode for a secondary battery according to claim 1, wherein each of the first negative electrode active material layer and the second negative electrode active material layer contains 50 parts by weight to 99 parts by weight of artificial graphite based on 100 parts by weight of the negative electrode active material.

11. A secondary battery comprising the negative electrode for a secondary battery according to claim 1 , a positive electrode, and a separator.

12. The secondary battery according to claim 11 , wherein the positive electrode contains a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material.

13. The secondary battery according to claim 12 , wherein the lithium composite transition metal compound further contains at least one of manganese and aluminum.

14. A method for producing a negative electrode for a secondary battery according to any one of claims 1 to 10, comprising the steps of: forming a first negative electrode active material layer on a current collector; and forming a second negative electrode active material layer on the first negative electrode active material layer; Including, the first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is 10 μm or less; The method further includes magnetically aligning the first and second negative electrode active material layers to adjust OI(004 / 110) to 8 or less.

15. The method of claim 14 , wherein a weight loading ratio of the second negative electrode active material layer is 20% to 35% of a weight loading ratio of the first negative electrode active material layer and the second negative electrode active material layer.

Citation Information

Patent Citations

  • Negative electrode plate and secondary battery comprising the same

    EP3462521A2

  • Secondary battery

    JP2013004307A

  • Lithium ion secondary battery

    JP2019175712A

  • Negative Electrode for Lithium Secondary Battery and Lithium Secondary Battery Including the Same

    US20210391570A1